Indonesian Language Minority in the Virtual Space of Indonesian People Majority: Virtual Linguistic Landscape of r/Indonesia Subreddit - Ayu Fitriawati; Frans Asisi Datang (Lensa: Kajian Kebahasaan, Kesusastraan, dan Budaya, 2023)
Through the study of Virtual Linguistic Landscape (LLV), this descriptive qualitative research aims to explore the contestation of Indonesian language in a virtual multilingual space with Indonesian people as the majority, namely the r/Indonesia subreddit community, within a social media site dominated by English speakers, Reddit. Each of the top-down contents made by the community moderators and bottom-ups made by the community members is observed. The analysis consists of the identification of the language dominance as well as the informational and symbolic functions behind the use of the languages in both types of content to further elaborate the significance of the dynamic. The research found that although members of the community are mostly Indonesian, English dominates all top-down contents. This domination functions informationally as a form of language accommodation while symbolically signifying that positive attitude is more assigned to English than Indonesian language as a status symbol. However, both English and Indonesian language dominate various different bottom-up contents. While the use of both languages also functions informationally as a form of language accommodation, the symbolic functions are more significant. That is, English as a marker of competence within the space designed for niche discussions and Indonesian language as a form of closeness and solidarity among members. Additionally, the use of English in the semi-formal bottom-up content indicates an influence of language choice by the top-down contents.